The Role of Intangible Features in Developing Open Spaces (The International Journal of Engineering & Information Technology (IJEIT), 2024)
this paper focuses on the role of intangibleelements of the public spaces in the residential areas such asa neighbourhood. The main emphasis is the significance ofthe factor of social satisfactions on developing public spaces.The research to date has tended to focus on examining thephysical quality of public space, particularly tangiblefeatures, but fewer have dealt with the intangible featuresthat related to the residents’ social life and communityinteraction. Consequently, in this research, the analysisincludes some important intangible elements such as a senseof community, social satisfaction and safety and security inthe public spaces and the local initiatives. The researchincludes two case studies in Misurata, Libya. Both cases areneighbourhoods type with similar in size, population,number of houses and distance from the city centre.However, one case is a Governmental Neighbourhood GNswhile the other one is a Traditional Neighbourhood TNs.This inquiry is a qualitative research, however, it adoptedmixed methods approach, and i.e. both questionnaires andin-depth interviews were utilized for data collection. Theresults of this study show that there are a several crucialfindings related to the importance of these intangibleelements, these findings suggest some practical guidelines tobe considered in new development projects.